(untitled) (Medico Legal Update, 2020)
Introduction: Various studies are carried out to improve posture and balance in children with cerebral palsy by using different approaches. But the aspect of vestibular stimulation exercises on improving posture and balance in children with CP have not yet been studied. Hence this study is design to see the effect of vestibular stimulation exercises on posture and balance in children with CP. Methodology: Thirty children with clinical diagnosis of Cerebral palsy, were randomly allocated into control group and interventional group. Participants in control group were given Conventional Physiotherapy. Participants in intervention group were given Conventional Physiotherapy and vestibular stimulation exercises. Results: The result of the study found extreme significant effects of the conventional physiotherapy in control group and extreme significant effects of conventional physiotherapy and vestibular stimulation exercises on posture and balance in children with CP in intervention group according to the results of the GMFM-88 and PBS. There is significant difference in mean score of GMFM-88 and PBS in intervention group as compared to the control group. Conclusion: There will be significant effect of vestibular stimulation exercises on posture and balance in children with CP.